2020
DOI: 10.1158/1541-7786.mcr-20-0292
|View full text |Cite
|
Sign up to set email alerts
|

HCN Channel Activity Balances Quiescence and Proliferation in Neural Stem Cells and Is a Selective Target for Neuroprotection During Cancer Treatment

Abstract: during cancer treatment. neural stem cells and is a selective target for neuroprotection HCN channel activity balances quiescence and proliferation in Updated version

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 54 publications
3
7
0
Order By: Relevance
“…These results indicate that, in addition to -and perhaps as a consequence of -a direct effect on NSC proliferation, a dysfunction in HCN subunits might also result in a dysregulated balance between neurogenesis and gliogenesis. A recent study found that both the application of ZD7288, or of the less specific Ih blocker Cs + , onto NSC cultures reduced the fraction of cells showing spontaneous Ca 2+ oscillations (23). Using slightly different experimental conditions such as a shorter observation time, we did not find systematic changes in Ca 2+ oscillations in our experiments with cultured rat NSCs upon ZD7288 application (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…These results indicate that, in addition to -and perhaps as a consequence of -a direct effect on NSC proliferation, a dysfunction in HCN subunits might also result in a dysregulated balance between neurogenesis and gliogenesis. A recent study found that both the application of ZD7288, or of the less specific Ih blocker Cs + , onto NSC cultures reduced the fraction of cells showing spontaneous Ca 2+ oscillations (23). Using slightly different experimental conditions such as a shorter observation time, we did not find systematic changes in Ca 2+ oscillations in our experiments with cultured rat NSCs upon ZD7288 application (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 59%
“…HCN channels are part of an evolutionarily old and conserved family of ion channels (55) that are expressed in different cell types with proliferative potential (56,57). A comparison of our HCNsubunit expression analyses with those of other studies and databases of embryonic mouse brain, stem cells, and induced human pluripotent stem cells has consistently revealed HCN3 to be the most abundant subunit (21,23,27,56,57). In addition to HCN3, the data also implicate HCN1 and HCN4 as potential HCN subtypes in the developing mouse and human fetal cerebral cortices (SI Appendix, Figs.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Furthermore, systemic, or local administration of ZD7288 suppresses neuropathic pain behavior as well as abnormal spontaneous firing in injured nerve fibers in rats, supporting the accumulating evidence that increased HCN channel activity is responsible for neuropathic pain ( Chaplan et al, 2003 ; Lee et al, 2005 ; Luo et al, 2007 ; Ding et al, 2018 ). Moreover, HCN channel inhibition with ZD7288 provides protection for neural stem cells during radiotherapy, suggesting new therapeutic strategies against neurocognitive damage caused by chemotherapy and radiotherapy in cancer patients ( Johard et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%